Case report: Blue rubber bleb nevus syndrome with Kasabach-Merritt phenomenon in a neonate - Pi, Mengqi; Zhao, Lei; Xu, Weiyang; Xu, Miao; Ding, Yu (Frontiers in Pediatrics, 2023)
Blue rubber bleb nevus syndrome (BRBNS) is a rare disease characterized by multifocal venous malformations that can affect any organ or tissue. Kasabach-Merritt phenomenon (KMP) is a serious and extremely rare complication of BRBNS. This report describes a neonate with BRBNS with KMP who was successfully diagnosed and treated with low-dose sirolimus and glucocorticoids. A 13-day-old female infant was born with multiple tumors on her head, neck, shoulder, back, abdomen, limbs, perineum, etc. some of which were blue. Laboratory examinations showed thrombocytopenia, anemia and coagulopathy. BRBNS with KMP was diagnosed. Oral low-dose sirolimus combined with glucocorticoids was administered. After 6 months of regular follow-up, the lesions in the child were significantly decreased, and there were no signs of KMP recurrence. The presence of KMP should be considered in patients diagnosed with BRBNS who present with thrombocytopenia, anemia and coagulopathy. Sirolimus combined with glucocorticoid therapy can be administered to save the patient's life.